An analysis regarding the relation between rationality and ethics on decision-making in organizations - Ojeda Pino , Jorge Luis (2020)
The decision-making process is a key element within many fields. Rationality is a theoretical framework to understand that social and economic behavior which contributes to better decisional processes. This role of rationality generates expectations from the stakeholders of the decisional process, one of which is refers to the need of including ethical criteria within the decisional process itself. This essay explores both the concept of rationality, as well as its types, in order to evaluate the extent to which ethical criteria should be part of said process. In doing this, the concepts of minimal instrumental rationality and ethics are analyzed, setting the stage for a discussion of common fields and roles in relation to both available knowledge before the decision-making, and reasoning, derived actions, and consequences. This essay concludes that rationality and ethics share much during the implementation of the decision-making process, though both have a different role in it.